The defense of sexual and reproductive rights of indigenous women of Colombia in UNO - Schmit, Anna (Universidad Pedagógica y Tecnológica de Colombia, 2015)
In Colombia rules since 1991 a new Constitution that recognizes, on the one hand, the multicultural character of the nation and, on the other one, the equality of women and men. Thus, it tends to produce a boundary between social categories, which discourages the exercise of the rights of the Indigenous female citizens. To remedy this legislative gap, in 2012, a local association of indigenous women’s human rights proposed to strengthen the alliance between the indigenous women of the country, around its first shadow report, which was presented to the Union Nation Comitee for the Elimination of Discrimination against Women (CoEDAW).